2016
DOI: 10.19185/matters.201610000014
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced plasticity of mature granule cells reduces survival of newborn neurons in the adult mouse hippocampus

Abstract: Dentate granule cells are born throughout life in the mammalian hippocampus. The integration of newborn neurons into the dentate circuit is activity-dependent, and structural data characterizing synapse formation suggested that the survival of adult-born granule cells is regulated by competition for synaptic partners. Here we tested this hypothesis by using a mouse model with genetically enhanced plasticity of mature granule cells through temporally controlled expression of a nuclear inhibitor of protein phosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 44 publications
0
2
1
Order By: Relevance
“…However, no rescue was achieved following restricted Cremediated recombination in either fully mature, pre-existing GCs, or more immature newborn GCs that did not yet reach 4 weeks of age, arguing in favor of mitochondrial fusion regulating competition dynamics specifically between adult-born GCs of similar age (4 to 6 weeks). This form of competition differs from previously proposed competition mechanisms between adultborn and pre-existing GCs, which appear to be specifically regulated during the third week of the cell age, namely at the beginning of excitatory innervation, when synaptogenesis peaks and dendritic spines are formed (Kleine Borgmann et al, 2016;McAvoy et al, 2016;Tashiro et al, 2006;Toni et al, 2007). In Mfn1 or Mfn2-deficient GCs, we find that spine formation and overall density are unaffected at all examined time points, suggesting that the initial stages of innervation and spinogenesis proceed as in control GCs.…”
Section: Discussioncontrasting
confidence: 65%
See 2 more Smart Citations
“…However, no rescue was achieved following restricted Cremediated recombination in either fully mature, pre-existing GCs, or more immature newborn GCs that did not yet reach 4 weeks of age, arguing in favor of mitochondrial fusion regulating competition dynamics specifically between adult-born GCs of similar age (4 to 6 weeks). This form of competition differs from previously proposed competition mechanisms between adultborn and pre-existing GCs, which appear to be specifically regulated during the third week of the cell age, namely at the beginning of excitatory innervation, when synaptogenesis peaks and dendritic spines are formed (Kleine Borgmann et al, 2016;McAvoy et al, 2016;Tashiro et al, 2006;Toni et al, 2007). In Mfn1 or Mfn2-deficient GCs, we find that spine formation and overall density are unaffected at all examined time points, suggesting that the initial stages of innervation and spinogenesis proceed as in control GCs.…”
Section: Discussioncontrasting
confidence: 65%
“…As competition between cohorts of GCs is regulated at the synaptic level (Kleine Borgmann et al, 2016;McAvoy et al, 2016;Tashiro et al, 2006), the transiently heightened synaptic plasticity of newborn GCs has been suggested to contribute to enabling their integration into the pre-existing circuits (Ge et al, 2007;Toni et al, 2007). To understand whether the enhanced mitochondrial fusion rates at the beginning of the critical period of plasticity may contribute to competition dynamics, we experimentally manipulated the extent of new GCs lacking Mfn2 by two independent approaches.…”
Section: Mitochondrial Fusion Regulates Competition Dynamics Between ...mentioning
confidence: 99%
See 1 more Smart Citation